2020
DOI: 10.1111/jgs.16681
|View full text |Cite
|
Sign up to set email alerts
|

Launching a Geriatric Surgery Center: Recommendations from the Society for Perioperative Assessment and Quality Improvement

Abstract: To prepare for the increasing numbers of older adults undergoing surgery, the American College of Surgeons (ACS) has recently launched the Geriatric Surgery Verification Program with the goal of encouraging the creation of centers of geriatric surgery. Meanwhile, the Society for Perioperative Assessment and Quality Improvement (SPAQI) has published recommendations for the preoperative management of frailty, which state that teams should actively screen for frailty before surgery and that pathways, including ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 23 publications
1
42
0
1
Order By: Relevance
“…With a noticeable increase in the aged population worldwide, there is a need to improve surgical care to maximize the positive outcomes and to minimize the burden of surgical comorbidities for the aged patient. The American College of Surgeons has recently introduced a geriatric surgery verification program suggesting standards for hospitals to provide better perioperative care for the aged and frail patients undergoing surgery [30]. One of the standards in the program is to advance the knowledge in geriatric surgery encouraging scholarly research in the improvement of the quality of geriatric surgery [31].…”
Section: Discussionmentioning
confidence: 99%
“…With a noticeable increase in the aged population worldwide, there is a need to improve surgical care to maximize the positive outcomes and to minimize the burden of surgical comorbidities for the aged patient. The American College of Surgeons has recently introduced a geriatric surgery verification program suggesting standards for hospitals to provide better perioperative care for the aged and frail patients undergoing surgery [30]. One of the standards in the program is to advance the knowledge in geriatric surgery encouraging scholarly research in the improvement of the quality of geriatric surgery [31].…”
Section: Discussionmentioning
confidence: 99%
“…Recent SPAQI recommendations for the preoperative management of frailty 35 as well those on launching a dedicated geriatric surgery center 36 have outlined specific steps and considerations in vulnerable populations undergoing elective surgery. This includes active screening for frailty as well as developing clinical pathways, and incorporating geriatric co-management, shared decision-making, and multimodal prehabilitation to improve postoperative outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…One study has shown that just a one-time session with a physical therapist to learn and practice postoperative precautions, exercises, bed mobility preoperatively achieved readiness to discharge from PT faster than the control group. 34 Recent SPAQI recommendations for the preoperative management of frailty 35 as well those on launching a dedicated geriatric surgery center 36 have outlined specific steps and considerations in vulnerable populations undergoing elective surgery. This includes active screening for frailty as well as developing clinical pathways, and incorporating geriatric co-management, shared decision-making, and multimodal prehabilitation to improve postoperative outcomes.…”
Section: Post-operative Decline In Independencementioning
confidence: 99%
“…It is important to understand the likelihood of an NHD for a patient who had been home-dwelling prior to elective surgical intervention because older patients continue to represent a larger share of patients presenting for elective surgery. Using risk factors identified from a broad population of older adults may help inform health care providers such as surgeons and anesthesiologists, primary care providers, and specialists of an individual's expected postoperative course should they decide to proceed with elective surgery and design preoperative evaluation pathways (Ogink et al, 2019;Cooper et al, 2020). Our study also offers information to facilitate preoperative shared decision-making, taking into account risks of the procedure and the patient's goals of care (Brovman et al, 2018;Quinn et al, 2018).…”
Section: Discussionmentioning
confidence: 99%